FROM SECURE DEPENDENCY TO ATTACHMENT Mary Ainsworth's Integration of Blatz's Security Theory Into Bowlby's Attachment Theory - van Rosmalen, Lenny; van der Horst, Frank C. P.; van der Veer, Rene (My University, 2016)
John Bowlby is generally regarded as the founder of attachment theory, with the help of Mary Ainsworth. Through her Uganda and Baltimore studies Ainsworth provided empirical evidence for attachment theory, and she contributed the notion of the secure base and exploratory behavior, the Strange Situation Procedure and its classification system, and the notion of maternal sensitivity. On closer scrutiny, many of these contributions appear to be heavily influenced by William Blatz and his security theory. Even though Blatz's influence on Ainsworth has been generally acknowledged, this article, partly based on understudied correspondence from several personal archives, is the first to show which specific parts of attachment theory can be traced back directly to Blatz and his security theory. When Ainsworth started working with Bowlby in the 1950s, around the time he turned to evolutionary theory for an explanation of his findings, she integrated much of Blatzian security theory into Bowlby's theory in the making and used her theoretical and practical experience to enrich attachment theory. Even though Blatz is hardly mentioned nowadays, several of his ideas live on in attachment theory.
Keywords: attachment theory; ainsworth; bowlby; blatz; security theory